Development of a Modified Adhesion Test for Hot-Poured Asphalt Crack Sealants. Issue 1 (2017) - Sawalha, Mohammed; Ozer, Hasan; Al-Qadi, Imad L.; Xue, Hengxiao
Crack sealing is a maintenance technique commonly used for cracks and joints to prevent moisture infiltration into pavements. Crack sealing materials should possess adequate adhesive and cohesive properties to remain intact in the cracks or joints, depending on the environment and pavement conditions in which they are installed. Adhesion failure is the most common failure mechanism and occurs mostly because of the poor adhesion capacity of sealants as well as the installation quality. Various standard laboratory tests are currently used to evaluate the adhesive properties of sealants to predict their field performance. These tests, however, either lack correlation with the field performance or have not yet been validated. This paper introduces the development of an adhesive prediction test: the modified crack sealant adhesion tester (modified CSAT). The modified CSAT is an improved version of the existing CSAT standard (AASHTO TP 89) and showed consistent results between specimens with sufficient repeatability. In addition, the modified CSAT was successful in capturing the effect of temperature changes and aging on the adhesion capacity of sealants. The adhesion test results were compared with the performance of the same sealants installed at different test sites. The correlation between the adhesion loads obtained in the laboratory was consistent with the sealant field performance.